2014
DOI: 10.1021/jm401138v
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Activity of Pyridopyrimidine Scaffolds as Novel PI3K/mTOR Dual Inhibitors

Abstract: The design, synthesis, and screening of dual PI3K/mTOR inhibitors that gave nanomolar enzymatic and cellular activities on both targets with an acceptable kinase selectivity profile are described. A docking study was performed to understand the binding mode of the compounds and to explain the differences in biological activity. In addition, cellular effects of the best dual inhibitors were determined on six cancer cell lines and compared to those on a healthy diploid cell line for cellular cytotoxicity. Two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 60 publications
(45 reference statements)
0
34
1
Order By: Relevance
“…To discovered novel PI3Kα/mTOR inhibitors, 2-amine-4- heterocyclic aryl-disubsituted pyrido[2,3-d]- and pyrido[3,2-d] pyrimidines with (158-161)were designed by Saurat et al [64] . Seven promising PI3Kα/mTOR dual inhibitors (IC 50 values <100 nM) were discovered, and two urea derivatives 162(PI3Kα/mTOR IC 50 = 58/5 nM) and 163 (PI3Kα/mTOR IC 50 = 40/1 nM) were further developed to enhance their efficacy.…”
Section: Pyrimidines and Quinazolinesmentioning
confidence: 99%
“…To discovered novel PI3Kα/mTOR inhibitors, 2-amine-4- heterocyclic aryl-disubsituted pyrido[2,3-d]- and pyrido[3,2-d] pyrimidines with (158-161)were designed by Saurat et al [64] . Seven promising PI3Kα/mTOR dual inhibitors (IC 50 values <100 nM) were discovered, and two urea derivatives 162(PI3Kα/mTOR IC 50 = 58/5 nM) and 163 (PI3Kα/mTOR IC 50 = 40/1 nM) were further developed to enhance their efficacy.…”
Section: Pyrimidines and Quinazolinesmentioning
confidence: 99%
“…Activation of the PI3K/Akt/ mTOR pathway is not vertical and it has been shown that mTOR exerts a negative feedback loop on PI3K. For this reason, inhibition of mTOR or PI3K alone is not sufficient to efficiently block this signaling pathway in cancer cells and a new strategy involved the combined inhibition of both enzymes [32,33].…”
Section: Design Of Pyridopyrimidines For Biological Activitymentioning
confidence: 99%
“…Furthermore, a relative selectivity could be of added value to a compound, bringing with it a potentially advantageous polypharmacological profile [11]. For instance, dual inhibitors of the PI3K/mTOR pathway have been found to be more efficient at inhibiting the proliferation of breast cancer cells than specific inhibitors of PI3K or mTOR [12, 13]. This demonstrates the importance of studying the selectivity profile of compounds as soon as possible in the discovery process.…”
Section: Introductionmentioning
confidence: 99%